The Implementation of Islamic Education through the Cultivation of Clean and Healthy Living Habits among Students at Raudlatul Ulum 2 Islamic Boarding School - Hakim Luqman; Nabila Ananda (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to examine the implementation of Islamic education through the habituation of a clean and healthy lifestyle among students at Raudlatul Ulum 2 Islamic Boarding School. The research employed a qualitative approach with a descriptive method to gain an in-depth understanding of the implementation of the program. The participants of this study consisted of the boarding school caretaker, administrators, female teachers (ustazah), and students. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing.The findings reveal that the habituation of a clean and healthy lifestyle is implemented through various routine activities, such as daily cleaning duties, communal cleaning activities (ro'an), maintaining the cleanliness of dormitory rooms and the boarding school environment, enforcing cleanliness regulations, and promoting healthy living habits. These programs are not only intended to create a clean, healthy, and comfortable environment but also serve as a means of instilling Islamic educational values in the students’ daily lives. Through these activities, students develop discipline, responsibility, cooperation, environmental awareness, and an understanding that cleanliness is an integral part of Islamic teachings. The success of the program is supported by clear boarding school regulations, the active role of administrators in guidance and supervision, the availability of adequate sanitation facilities, and strong cooperation among students. However, several challenges remain, including the low awareness of some students, differences in habits before entering the boarding school, and the large number of students, which makes supervision less optimal. Therefore, the clean and healthy lifestyle habituation program at Raudlatul Ulum 2 Islamic Boarding School has proven to make a positive contribution to the development of students’ character based on Islamic educational values.